Microhydrodynamics and Complex Fluids. - Barthès-Biesel, Dominique (CRC Press, 2012)
""In view of the good choice of highly topical subject matter, the book will be of interest to a wide readership, not only among pure scientists. It will be useful to technicians, medical scientists and pharmaceutical chemists as a source of detailed information on advanced flow processes. ... [The chapters] are written in such a way that the reader can quickly absorb the essential information. The articles are of a high scientific standard and include interesting examples from many different areas of rheology.""--Prof. Dr. Heinz Rehage, Institute of Physical Chemistry, Technische Universität.